Protection of the Rights of Parties to a Construction Contract Under the Laws of Singapore and Thailand - E. V. Belousova (Сибирское юридическое обозрение, 2023)
The institute of protection of rights of construction contractors and customers under the legislation of the Republic of Singapore and the Kingdom of Thailand is considered.   The purpose of the article is a comparative legal analysis of the ways of protection of the rights of parties to construction contracts in these states.   The article presents a comprehensive view at this issue from a legal point of view. The normative basis for regulating the construction industry in Singapore and Thailand includes Civil codes and special legal acts (construction laws, by-laws of ministries and departments). Protection of rights includes measures of responsibility, measures of protection, measures of operational influence and measures of self-defense. Such methods of protection as reco very of liquidated damages, unjust enrichment, special contractual clauses, suspension of fulfillment of obligations and others are analyzed. It is noted that recovery of liquidated damages is a common method of protection of rights in foreign countries. However, this method is not typical for the Russian Federation. Unjust enrichment and restitution are considered equivalent and interrelated concepts applied in various relations, including construction. Self-protection measures include the inclusion of various clauses in construction contracts, suspension of fulfilment of obligations. The parties have the right to stipulate in the contract a condition of exclusion or limitation of liability, if such a condition is not prohibited by law. In the states in question, the rights of construction clients and contractors may be protected through various bodies. Most often construction disputes are resolved in courts or in arbitration. It is concluded that the legal regulation of protection of the rights of the parties to a construction contract in these states was formed under the influence of both continental and Anglo-Saxon legal families. At the same time, these countries have their own customs and traditions, that are unique and original. Based on the conducted research, a proposal for reforming the current civil legislation of the Russian Federation in terms of protection of the rights of construction contractors has been formulated.